Calibration of sprinkler to simulate tropical rainfall - Murugaboopathi, C.; Jensen, Jens Raunso; Eppendorfer, W.H.; Rahman, Md. Ataur; Canadian International Development Agency, (CIDA-BBD) (Bangkok : Asian Institute of Technology, 1985)
The study aims at calibrating sprinkler nozzles to simulate tropical rainfall with respect to rainfall characteristics such as intensity. distribution uniformity, dropsize distribution, kinetic energy and momentum. The "Rainjet 836c" square pattern sprinkler nozzle was selected for this purpose. One, two, three and four nozzle arrangements were used and the rainfall of different intensities was obtained by varying the gate valve pressure. The simulated rainfall was within the intensity range of 18.84mm/hr to 95.05mm/hr and the distribution uniformity was between 75.68 percent to 93.26 percent. The relationship between the drop mass and pellet mass was investigated using a drop forming apparatus and a "Mass Ration Curve" was developed, showing the relationship between pelletmass and massratio, the ration of the drop mass to pelletmass. The mass ratio curve was used to analyse the dropsize distribution of the simulated rainfall. Eight sets of measurements were made for the dropsize distribution and the results imply that the distribution of the drops follows the Gumbel distribution. The median volume drop diameter ranges between 1.69mm -2.15 mm. The kinetic energy and momentum of the simulated rainfall were also evaluated and momentum of the simulated rainfall were also evaluated and the values obtained are much higher than for actual rainfall because of the pressure and velocity energy in the nozzle.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1985
Keywords: Rain-making